(untitled) (Journal of Engineering Science, 2024)
Chitosan biopolymer has been used as a key supporting material for the synthesis of metallic nanoparticles (MNPs) due to its exceptional qualities, which include good capping and stabilizing capabilities, biocompatibility, biodegradability, eco-friendliness, polycationic and non-toxicity. In this study, chitosan-based metal nanoparticles, such as copper nanoparticles (Chi-Cu NPs) and zinc nanoparticles (Chi-Zn NPs) have been synthesized, characterized and checked for their bacteriological properties. The solution casting method has been employed to produce metal nanoparticles based on chitosan. FTIR, TGA, and SEM analysis were employed to characterize the produced nanoparticles. The produced materials are nanomaterials with a size range of 1-100 nm, as demonstrated by the SEM photograph. The generated nanoparticles showed increased antimicrobial activity. Chi-Zn NPs have zones of inhibition of 38, 31, 30 and 39 and Chi-Cu NPs have zones of inhibition of 32, 36, 37 and 32 mm against Pseudomonas aeruginosa, Salmonella bovismorbificans, Salmonella typhi and Escherichia coli bacteria, respectively. Whereas the standard medication kanamycin have zones of inhibition 22, 22, 20 and 20 against those bacteria, respectively. Journal of Engineering Science 15(1), 2024, 45-57